Optimization of Red Pigment Production By Monascus Purpureus FTC 5356 Using Response Surface Methodology - Nor Farhana, Hamid; Farhan, Mohd Said (IIUM, Malaysia, 2018)
Important factor such as certain environmental conditions and nutrients as a source for the medium are significant for successful growth and reproduction of microorganism. Manipulation of the factor is the most effective way to stimulate the growth of the microorganism in subsequent optimize the quality of the product. In this study, Central Composite Design (CCD) of Response Surface Methodology (RSM) was used to optimize the production of red pigment by Monascus purpureus FTC 5356 using oil palm frond (OPF) as a substrate in solid state fermentation (SSF). The data was analyzed using Design Expert Software. The optimum combination predicted via RSM was confirmed through experimental. The interaction between three variables ie; initial moisture content (%), initial pH value (pH), and peptone concentration (%) was studied and modeled. The statistical analysis of the results showed that in the range studied, optimal condition for red pigment production (47 AU/g) with the biomass (425.1 mg/g) was 55% initial moisture content, 3% of peptone concentration and pH 3 for initial pH value of the substrate. The results of RSM showed that the initial pH value had significant effect on red pigment production (P-value <0.05). The validation of these results was also conducted by carried out fermentation with predicted condition and it was found that there are 0.373% higher in values of experimental result compared to the predicted values.